Assessment of the wave energy resource in the South China Sea. Issue 1 (15th May 2019) - Jiang, Bo; Wu, Guowei; Ding, Jie; Ma, Changlei; Fang, Yizhou; Wang, Xiaoyng
Abstract : Assessments of wave energy resources form the basis of plans for developing and using wave energy, and provide guidance about where to site wave power stations and how to design wave energy convertors. Various indexes, including the spatial and temporal distributions of wave energy fluxes, the occurrence of the effective significant wave height, monthly and seasonal variability and the frequency of high sea states, were calculated from the recent 37-year European Centre for Medium-Range Weather Forecasts ERA-Interim reanalysis of wave field data. The results showed that areas with abundant and stable exploitable wave energy in the South China Sea were mainly between the Luzon Strait and the southeast of the Indo-China Peninsula, where the annual average wave energy fluxes ranged from 10 to 18 kW/m and the monthly and seasonal variability indexes were less than 2·2 and 1·6, respectively. The wave energy was found to be poor in some coastal areas of the Beibu Gulf, the Gulf of Thailand and the Sulu Sea. In the areas where wave energy was abundant, high sea states occurred frequently, meaning that it was relatively difficult to use the energy. Therefore, the wave energy resources and the frequency of high sea states need to be considered when choosing sites for wave energy farms.